Risk factors and mortality profile of post neonatal deaths; 1 month to 1 year, in a rural medical college hospital, South India - Balamurugan, Kuppan; Ponprabha, Rajangam; Sivashankari, Veeramani (International Journal of Research in Medical Sciences, 2021)
Background: Infant mortality is the most important indicator which reflect country growth standards and development. This study was aimed to assess the risk factors and clinical profile of post neonatal deaths, admitted in PICU, government Villupuram medical college. Methods: A retrospective analysis was done on post neonatal mortality data by pediatric department of government Villupuram medical college, Mundiyambakkam from January 2019 to December 2020, referral and LAMA patients were excluded from study. Data was analyzed using SPSS 18.0 Results: Overall post neonatal mortality was 7.3%. Mortality amongst boys were 28 (41.1%) and girls were 40 (58.8%). Mortality of female babies were higher than male babies. Among the 68 post neonatal deaths, maximum number of mortalities was seen in 1-3 months (61.9%), maximum within 24 hours of hospital stay (54.4%), 37 cases (54.4%) were referred from GHPHC and private practitioners of the nearby districts, 28 babies (41.1%) had previous admissions, 22 babies had SNCU admissions and 6 babies had pediatric admissions. Three most common causes of mortality were bronchopneumonia, sepsis and acute CNS infections. Congenital malformations and heart disease along with failure to thrive are other causes of morbidity. Conclusions: Analysis reflects the disease occurrence, treatment modalities and quality of treatment available. Treatment at primary level can prevent postnatal deaths from infections. The preventive and primary health care system should be strengthened. All special newborn care units (SNCU) discharged babies should have both community and district early intervention centre (DEIC) follow up, immunization practices, explaining danger signs to the parents, improving the quality of life has got great impact on the post neonatal outcome.